Keberfungsian Model ABC Tschudi untuk Internalisasi Budaya Belajar Mahasiswa - Mappiare-AT, Andi; Fauzan, Lutfi (Jurnal Kajian Bimbingan dan Konseling, 2019)
This research aimed to find: (1) the difficulties possibly faced by subjects in managing personal construct when filling Tschudi ABC format; (2) key personal construct recognized by subjects in their present and desired positions; (3) the results of subjects’ learning culture internalization to the implementation of Tschudi ABC Model. This study used a qualitative approach with the type of Classroom Action Research, the empirical phenomenological variant. The observed subjects were determined by purposive sampling, taken from the students of Multicultural Counseling class. The research informants were determined through snowballing. The data collection was conducted via a medium participatory observation and in-depth interview. The individual analysis was employed in the form of dynamic analysis of the research subjects’ individual personality. This research found that: (1) there was a difficulty in the form of contradiction and disparity in personal construct management. According to the subjects, compromise and synchronization of thoughts and attitudes were effective in settling the self-denial and gap; (2) The tendency of the change of subjects’ key personal construct was intentional accompanied by discursive awareness versus withdrawal and stagnant. There was a change of key personal construct to the more productive and non-productive orientation; (3) The function of “good news” versus “bad news” was very strong in the internalization of subjects’ learning culture. Providing “good news” (positive feedback) gave rise to more non-formal and affective internalization of learning culture with the purpose stated consciously and obviously, as well as concrete, clear, decisive, and straightforward plans.